Studies of the Influence of Gold Nanoparticles on Characteristics of Mesenchymal Stem Cells. (24th October 2017) - Volkova, Nataliia; Pavlovich, Olena; Fesenko, Olena; Budnyk, Oksana; Kovalchuk, Serhii; Goltsev, Anatoliy
Abstract : The aim of the present study is to determine what effect the different concentrations of 15 nm gold nanoparticles (AuNPs) will have on the immunophenotype, synthesis collagen type I, ability to direct differentiation and spectroscopic characteristics of bone marrow mesenchymal stem cells (MSCs). The AuNPs in concentrations of 1.5–9 μ g/ml did not lead to changes in the level of expression of CD 45, CD 90, and CD 73. It should be noted that AuNPs in concentrations of 6 and 9 μ g/ml led to a decrease in CD 44 cells by 6% and 9%, respectively. The content of CD 105 cells was reduced by 5% when AuNPs were applied at a concentration of 9 μ g/ml. It was found that AuNPs in concentrations of 1.5–6 μ g/ml are safe for MSCs, while the increase up to 9 μ g/ml has a toxic effect, manifested by the reduction of synthesis collagen type I and ability of adipogenic differentiation. IR spectroscopy data have shown that the AuNPs at concentrations of 9 μ g/ml under conditions of adipogenic differentiation to MSCs lead to the destruction processes in the cells. The obtained results are related to the field of applied nanotechnology, which extends to regenerative medicine, especially in development of bioimplantology.